Odyssey - Homer; Butler, Samuel Tr. (Singapore Penguin Random House, 2024)
Sequal to The Illiad, the story begins ten years after the Trojan War and the Fall of Troy, when Odysseus, one of the war heroes, has still not returned to his kingdom Ithaca. The Odyssey, which means the story of Odysseus, highlight another universal truth about life which is the desire to return home, the destructions and sacrifices of war. When assumed dead, Odysseus$1 (Bs wife Penelope and son Telemachus struggle with a group of unruly suitors who have overrun their palace wanting to marry Penelope and take over his house. But Odysseus is still alive; imprisoned on the island of Ogygia by Calypso, who is possessed by love for him and desires to make him her immortal husband. Homer$1 (Bs epic poem, larger than life emotions, and philosophical thoughts is a reminder of the bitter-sweet melancholies and the simplest desires of life.s
Keywords: English Stories; Story of Trojan War